Development of dietary fiber enriched chicken nugget using wheat bran - Nahid, MZA; Habib, M; Mollah, MBR; Hashem, MA; Azad, MAK; Ali, MS (Meat Research, 2024)
An experiment was conducted to find out the effect of different levels of wheat bran on the sensory, oxidative stability, physicochemical properties in different storage period of broiler meat nugget. For this purpose, nuggets were prepared in 3 different groups. They were T1 (chicken nugget incorporated with 0% wheat bran), T2 (chicken nugget incorporated with 5% wheat bran), T3 (chicken nugget incorporated with 10% wheat bran). All parameters were analyzed at 0th, 14th and 28th days. The sensory evaluation was evaluated at day one. The proximate composition of different nuggets was analyzed and highly significant differences were found in CP (%) and CF (%). Significantly, higher CF (%), Ash (%) were found in T3 , while CP (%) was significantly higher in T1. No significant differences were found in EE (%) and DM (%) among the treatments. Storage period had highly significant on CP only. CP (%) content is increased with increase of storage period. The surface color (CIE L*, a*, b*) of nugget samples were measured. Significantly, the highest lightness value was found in T1 and lowest value was found in T3 . Storage period had an effect on lightness value also. Increasing the storage value lightness decreased. Treatment had no effect on pH, but storage period had effect on pH. Significantly, lower pH was found in 14th days of storage period. During biochemical analysis, it was found that treatment had no effect on free fatty acid value (FFA) and per-oxide value (POV) but had effect on Thiobarbituric acid reactive substances (TBARS). However, storage period had effect on FFA, POV and TBARS value. Increasing the storage period FFA, POV and TBARS values increased. During sensory analysis, all parameters including overall acceptability did not differ among the treatments concluded that wheat bran up to 10% could be used in nugget preparation with no change in consumer acceptance.